THE ROLE OF INSTAGRAM IN THE PRESERVATION AND PROMOTION OF TRADITIONAL BATAK TOR-TOR DANCE (A Case Study On The @zonabatak Account) - Winda Kustiawan; Fauzul Azmi Daulay; Amelia Lestari Butar Butar; Muammar Dzaki Ihsan (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
The development of information and communication technologies has significantly influenced the dynamics of cultural preservation in the digital era. Social media, as one of the products of this era, has emerged as a strategic medium for disseminating local cultural values to a broader, interactive, and more efficient audience. Among these platforms, Instagram stands out due to its strong visual orientation, which allows for creative and engaging cultural messaging, particularly targeting younger generations who dominate social media usage. In the context of Batak culture, the Tor-Tor dance represents an intangible cultural heritage with deep symbolic, spiritual, and social values embedded in traditional community structures. This dance functions not only as a form of artistic expression but also as a medium of communication between humans, ancestors, and deities. However, globalization and declining interest among youth have threatened its continuity. In response, the use of social media particularly Instagram accounts like @zonabatak has become a strategic means of preserving and promoting this cultural heritage. This study employs a descriptive qualitative approach to examine how the @zonabatak Instagram account utilizes features such as photos, videos, captions, stories, and user interactions to generate cultural awareness and disseminate information related to the Tor-Tor dance. The findings indicate that the account effectively presents visual content and contextualizes the dance in traditional rituals and youth education. In addition to conveying cultural knowledge, the account acts as a digital space for education and promotion, reaching audiences from various backgrounds. Interactive features such as comments and story polls further enhance Instagram’s role as a participatory and dynamic cultural communication platform. Although certain limitations exist such as inconsistent visual quality the account successfully communicates cultural values, stimulates curiosity, and fosters local cultural pride. Thus, @zonabatak serves as a concrete example of how social media can function as a tool for cultural preservation that aligns with contemporary digital communication practices.